Aplikasi Metode Markov Chain untuk Meningkatkan Tingkat Persediaan Bahan Baku yang Optimal - Umar Wiwi Wahyu Eni Maryati (Department Industrial Engineering, University of Muhammadiyah Malang, 2000)
Organize company stocks, it's very important thing that company must be done, because operation cost is depend on how company organize their stock. And lock of stock it's can anoycny an such as production at activities company. PT. Domusindo Perdana is a company that makes product such as furniture to full fill consument needed. That company must be ready stock one's of their produck because they can't guess wahat consument . Want's it's can makes a level of stock hot optimal depend on this phenomena, on this thesis will explain a production that using the right methode that finally can calculate stock at company that will be asking with consument and for calcuiate cost of stock, it's will be using Markov Chain methode.